Enhancing Critical Thinking and Written Communication Skills through Problem-Based Learning Assisted by Virtual Labs - Valina Yolanda; Muhammad Nasir; Fakhruddin (Jurnal Penelitian Pendidikan IPA, 2025)
This research investigates the effectiveness of the Problem-Based Learning (PBL) model assisted by virtual laboratories in improving critical thinking and written communication skills among students of MAN 2 Kota Pekanbaru. Utilizing a classroom action research (CAR) design across two cycles, this study focuses on the application of PBL with PhET Simulations. Results reveal significant improvements in both critical thinking and written communication skills. Key findings emphasize the integration of PBL and technology as effective tools for modern physics education. This study concludes with recommendations for broader adoption of virtual labs to address resource limitations and enhance active learning in science classrooms.